MECHANISM IN LEGAL ASSISTANCE FOR CRIMINAL CASES AT THE OFFICE OF ADVOCATE ARIEF BIJAKSANA LAW CORPORATION - Nadila Agatha Fristy; Agustianto Agustianto (ConCEPt - Conference on Community Engagement Project, 2022)
Arief Bijaksana Law Corporation is a company that is steeped in the field of Legal Services or is a Legal Consultant who handles all matters of criminal and civil cases handled by lawyers/advocates, this office is located at Ruko Mega Legenda Blok E1 number 23-24, Batam, Islands Riau, Indonesia.The main topic that will be discussed in this practical work report is the process/mechanism in legal assistance for criminal cases at the advocate's office at PT. Arief Bijaksana Law Corporation with the research method carried out to complete the report data, then it is done by going directly to the field and the data collection method is through observation in order to obtain the data to be achieved.